The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/0001-3765201620160041
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Cytotoxicity Effect of Ethanolic Extract of Spondias tuberosa Arruda Bark: Hematological, Biochemical and Histopathological Evaluation

Abstract: Spondias tuberosa Arruda, popularly named as umbu, is native from savanna-like vegetation and widely used for medicinal purposes, however, the toxicological profile is not available yet. This study evaluated the phytochemical profile and acute toxicity and citoxicity of Ethanolic Extract of Spondias tuberosa Arruda Bark (EEStb) in hematological, biochemical and histopathological parameters. Female Wistar rats were divided into: control (C) and animal treated single doses of 300mg/Kg (EEStb 300 ) or 2.000mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Phytochemical studies carried out with the species Myracroduo nurundeuva Allemão, Schinus terebinthifolius Raddi, Spondias mombin L., Spondias purpurea L. and Spondias tuberosa Arruda, belonging to the Anacardiaceae family, detected the presence of several secondary metabolites. The most abundant are phenols, triterpenes, flavonoids, and cinnamic acid, which are responsible for their anti-inflammatory action [ 53 , 54 , 55 ].…”
Section: Plant Use and The Development Of Drugsmentioning
confidence: 99%
“…Phytochemical studies carried out with the species Myracroduo nurundeuva Allemão, Schinus terebinthifolius Raddi, Spondias mombin L., Spondias purpurea L. and Spondias tuberosa Arruda, belonging to the Anacardiaceae family, detected the presence of several secondary metabolites. The most abundant are phenols, triterpenes, flavonoids, and cinnamic acid, which are responsible for their anti-inflammatory action [ 53 , 54 , 55 ].…”
Section: Plant Use and The Development Of Drugsmentioning
confidence: 99%
“…Several anti-inflammatory medicinal plant species, such as Myracroduo nurundeuva Allemão, Schinus terebinthifolius Raddi, Spondias mombin L., Spondias purpurea L., Spondias tuberosa Arruda, Euphorbiaceae acalypha hispida Burm. f., Acalypha indica L. and Phyllanthus niruri L. [ 4 , 9 , 38 , 47 , 54 , 61 ]. The authors reported that it may be due to the presence of phenols, triterpenes, flavonoids, saponins, and tannins in their extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of hematological parameters is a good predictor of the toxic potential of drugs, as blood cells are the first cells to be exposed to drug toxicity (Barbosa et al. 2016 ). The results of the present study demonstrated that the administration of 0.6 g/kg 2036S-QXR for 26 weeks increased the RBC count and HB level in the treated male rats compared with the control male rats.…”
Section: Discussionmentioning
confidence: 99%